2022
DOI: 10.1038/s41467-022-29434-x
|View full text |Cite
|
Sign up to set email alerts
|

High-performance hysteresis-free perovskite transistors through anion engineering

Abstract: Despite the impressive development of metal halide perovskites in diverse optoelectronics, progress on high-performance transistors employing state-of-the-art perovskite channels has been limited due to ion migration and large organic spacer isolation. Herein, we report high-performance hysteresis-free p-channel perovskite thin-film transistors (TFTs) based on methylammonium tin iodide (MASnI3) and rationalise the effects of halide (I/Br/Cl) anion engineering on film quality improvement and tin/iodine vacancy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 61 publications
0
56
0
Order By: Relevance
“…Not long ago, the hysteresis effect in a p-type MASnX 3 perovskite FET was exceptionally reduced by the halide anion engineering [ 131 ] of the hybrid halide perovskite channel using bromide and chloride co-substitutions or partial iodide. In this study, it was observed that the co-substitution of the anions enhanced the quality of the film and reduced the vacancy defects as well.…”
Section: Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Not long ago, the hysteresis effect in a p-type MASnX 3 perovskite FET was exceptionally reduced by the halide anion engineering [ 131 ] of the hybrid halide perovskite channel using bromide and chloride co-substitutions or partial iodide. In this study, it was observed that the co-substitution of the anions enhanced the quality of the film and reduced the vacancy defects as well.…”
Section: Challengesmentioning
confidence: 99%
“…As a result, the hysteresis effect was significantly reduced to a negligible level (0.1 V) in the transfer characteristics curves of Cl − and Br − incorporated MAPBI 3 channels, whereas the pristine MASnI 3 channel showed a notable 1.5 V difference between the forward and backward sweeps in the transfer curves. The mobility variation ratio of the forward and backward sweeps was reduced to 20% for Cl- and Br-incorporated MAPBI 3 -based FETs from the 45% of the pristine MASnI 3 channel FET [ 131 ]. Y. Liu et al reported that the hysteresis effect increases notably with the addition of SnI 4 to the (PEA) 2 SnI 4 channel; nevertheless, an enhancement was observed in the device current and on/off ratio [ 162 ].…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early research of perovskite-type transistors, two-dimensional organic–inorganic hybrid perovskite was used to prove the field-effect mobility of up to 2.6 cm 2 /V·s. In the latest research, H. Zhu et al demonstrated a high-performance hysteresis-free p-channel perovskite TFT with methylammonium tin iodide (MASnI3), and rationalized the effects of halide(I/Br/Cl) anion engineering [ 109 ]. This TFT has excellent electrical characteristics, with high hole mobilities of up to 20 cm 2 /V·s, an on/off current ratio exceeding 10 7 , and a threshold voltage of 0 V.…”
Section: P-type Oxide Film Progress and Challengesmentioning
confidence: 99%
“…Particularly, organic–inorganic perovskites have high intrinsic charge carrier mobilities that make them promising candidates for channel materials in field-effect transistors. High performance has been achieved in three-dimensional (3D) perovskite field-effect transistors , along with remarkable progress in perovskite solar cells. Derived from their 3D analogues, two-dimensional (2D) Ruddlesden–Popper (R–P) layered organic–inorganic perovskites show improved water and oxygen stability as well as thermal stability under the protection of bulky hydrophobic organic cations.…”
Section: Introductionmentioning
confidence: 99%